Training on Preparing a Balanced Nutritional Food Menu During Fasting for Cheerful Mutiara Cadres of Sungai Andai, Banjarmasin City - Ari Widyarni; Elsi Setiandari Lely Octaviana; M. Bahrul Ilmi; Edy Ariyanto; Netty Netty; Husnul Khatimatun Inayah; Noorhidayah Noorhidayah; M. Febriza Aquarista (Jurnal Medika: Medika, 2026)
Fasting is practiced by Muslims, especially during the month of Ramadan. Fasting is believed tohave numerous benefits and is a form of therapy (fasting therapy) for curing several degenerativediseases. People in Banjarmasin City often eat foods high in fat and sugar during fasting, andmany use excessive amounts of food coloring and flavoring. Lack of knowledge about healthyeating habits during fasting is a factor that can affect health. This has resulted in an increase indegenerative diseases such as hypertension, cholesterol, heart disease, and diabetes mellitus. Thiscommunity service program aims to improve the knowledge and skills of mothers, who play a rolein providing food for their families and developing nutritious diets, based on the awareness of theimportance of balanced nutrition according to the "isi piringku" guidelines established to reducethe morbidity rate of degenerative diseases. The implementation method includes a pretest,nutrition education, and training in developing balanced nutritional menus during fasting,followed by a posttest to measure the success of the activity. The community service programinvolved mothers from the Mutiara Ceria Integrated Health Post (Posyandu) and several elderlypeople at risk of developing degenerative diseases. The results showed an increase in knowledgeabout balanced nutrition, from 17% to 82%. The skills of cadres can be improved through trainingin preparing balanced nutritional meals during fasting. Optimizing health and nutrition education,especially regarding food menus during fasting, thereby increasing public understanding andawareness in preventing degenerative diseases and improving public health status.